Reciting Surah al-Kahf in the Month of Ramadan: A Case Study of Live Streaming on Instagram by Dompet Dhuafa Community Media - Wahyuni, Yuni (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2023)
This article delves into the recitation of Surah al-Kahf on the live streaming Instagram account of the Dompet Dhuafa community during the Ramadan program. The practice of reading Surah al-Kahf is recommended as one of the Sunnah practices, particularly on Fridays, as established by the hadith of Prophet Muhammad. This phenomenon continues to evolve within society. The research adopts a library research approach and utilizes Stuart Hall's encoding-decoding theory to analyze the phenomenon of reading Surah al-Kahf. The aim is to assess the alignment of the intended message by the video producer with the message perceived by the audience. The research findings reveal two interpretative meanings, in accordance with Stuart Hall's theory of encoding. The first is the dominant position, where the informant advocates for the recitation of Surah al-Kahf as a Sunnah to be performed every Friday. The negotiated position, on the other hand, reflects the informant's belief that reading Surah al-Kahf is indeed a Friday Sunnah, but simultaneously holds a differing perspective. The intended message of the video producer, presenting the recitation of Surah al-Kahf during Ramadan through live Instagram streaming, effectively reaches the audience. This conclusion is drawn from the response of informants who incorporate the recitation of Surah al-Kahf as a regular practice on Fridays, extending beyond the month of Ramadan.